Correlation of Eating Habits and Physical Activity with BMI - Samia Sarwar, Iram Qamar, Hira Malik, Farrukh Sarfraz, Hassan Jamil, Qurratulain Mehfooz, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: As life changes and gets to be more developed there are a lot of wellbeing issues and illnesses immerge. One of these major wellbeing issues is weight. About 20–40% of adult and 10–20% of children around the world are obese. Overweight and weight are characterized as abnormal or excessive fat aggregation which will impair health. Body mass index (BMI) is utilized to classify overweight and weight in grown-ups. It is person’s weight in kilograms divided by the square of his height in meters (kg/m2). Calculated BMI greater than or rise to to 25 is considered overweight; whereas weight is considered when BMI is equal or more than 30. Objective: To determine the levels of physical activity and patterns of dietary habits and their associations with BMI among the undergraduate medical students Material and Methods Study design: Quantitative cross sectional Settings: Rawalpindi Medical University Rawalpindi Duration: Four months i.e. 1st January 2022 to 30th April 2022 Data Collection procedure: Cross sectional was conducted on 200 medical students. Data was collected by validated questionnaire. Stratifies random sampling was done. Physical activity was calculated by International physical activity questionnaire and three factors eating were used to calculate the eating patterns of medical students. Data was analyzed by using SPSS version 22. Means standard deviation and percentages were calculated. Correlation between BMI and Physical activity and eating patterns were analyzed. P value was significant <0.005 Results: As far the results the total number of medical students was 200 in which 92 were males and 108 females. Students selected from all levels of MBBS. The prevalence regarding obesity among the medical students was 7.5%; overweight 12.5% and 10% was under weight. There was no significant relationship between BMI level and physical activity however the relation is significant between BMI and eating patterns (P= 0.01) Conclusion: In conclusion, low physical movement level and unhealthy eating patterns among medical study empowers implementation of wellbeing instruction programs about obesity and risk components among medical students. Extracurricular physical sports and activities ought to be executed by the organizations to empower students to be more physically dynamic in specific among female students. Keywords: Obesity, Eating patterns, Physical activity, BMI, Medical Students